2022
DOI: 10.1111/ecc.13733
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders' perceptions of a community‐based advanced nurse practitioner‐led integrated oncology care model for adults receiving oral anti‐cancer medication—A qualitative study

Abstract: Oral anti-cancer medications (OAMs) are increasingly prescribed in oncology, and although administered at home, ongoing monitoring generally requires the patient to attend an acute hospital. With the requirement to provide safe yet convenient care and to increase hospital capacity, the potential exists to transition this cohort of patients to the community to be assessed by oncology health care professionals (HCPs). The onset of COVID-19 facilitated this planned transition.Objective: The primary objective was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Our prior qualitative study found that patients have a desire for the same HCP to assess them at each clinic visit (Richmond et al, 2022b), something guaranteed in the ANP-led clinic. In addition, as patients received their rst 2 cycles of OAM treatment in the acute hospital setting, they had already experienced exceptionally long wait times of 3-4 hours (most of which was waiting for blood results/ to be reviewed by a doctor), compared to approximately 45-minutes in the ANP-led clinic.…”
Section: Implications For Patient Recruitment and Retention In A De N...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior qualitative study found that patients have a desire for the same HCP to assess them at each clinic visit (Richmond et al, 2022b), something guaranteed in the ANP-led clinic. In addition, as patients received their rst 2 cycles of OAM treatment in the acute hospital setting, they had already experienced exceptionally long wait times of 3-4 hours (most of which was waiting for blood results/ to be reviewed by a doctor), compared to approximately 45-minutes in the ANP-led clinic.…”
Section: Implications For Patient Recruitment and Retention In A De N...mentioning
confidence: 99%
“…This enabled development of best practice standards, clinical guideline and audit tools (Richmond et al, 2022a) and a base-line audit was performed (Richmond et al, 2023). Thirdly, to determine the acceptability of ANP-led care and possible transition to an integrated context, a qualitative study was performed which involved all relevant stakeholders (Richmond et al, 2022b). Analysis of the data using thematic analysis generated four themes resulting in agreement that an integrated model of ANP-led care had signi cant bene ts for patient care and the wider organisation of clinical oncology (Richmond et al, 2022b).…”
mentioning
confidence: 99%
“…Oncology is an increasing area of practice for Advanced Practitioners. Richmond et al [31] explore stakeholders' perceptions of a community-based ANP-led integrated oncology care model for adults receiving oral anti-cancer medication in an Irish hospital (n = 33). This study demonstrates that patients and health care providers (HCPs) perceived the proposal positively.…”
Section: Kelly and Horrigan Kellymentioning
confidence: 99%